Gender-Affirming Hormone Therapy Modifies the CpG Methylation Pattern of the ESR1 Gene Promoter After Six Months of Treatment in Transmen. Issue 9 (4th July 2020) - Fernández, Rosa; Ramírez, Karla; Gómez-Gil, Esther; Cortés-Cortés, Joselyn; Mora, Mireia; Aranda, Gloria; Zayas, Enrique Delgado; Esteva, Isabel; Almaraz, Mari Cruz; Guillamon, Antonio; Pásaro, Eduardo
Abstract: Background: Brain sexual differentiation is a process that results from the effects of sex steroids on the developing brain. Evidence shows that epigenetics plays a main role in the formation of enduring brain sex differences and that the estrogen receptor α ( ESR1 ) is one of the implicated genes. Aim: To analyze whether the methylation of region III (RIII) of the ESR1 promoter is involved in the biological basis of gender dysphoria. Methods: We carried out a prospective study of the CpG methylation profile of RIII (−1, 188 to −790 bp) of the ESR1 promoter using bisulfite genomic sequencing in a cisgender population (10 men and 10 women) and in a transgender population (10 trans men and 10 trans women), before and after 6 months of gender-affirming hormone treatment. Cisgender and transgender populations were matched by geographical origin, age, and sex. DNAs were treated with bisulfite, amplified, cloned, and sequenced. At least 10 clones per individual from independent polymerase chain reactions were sequenced. The analysis of 671 bisulfite sequences was carried out with the QUMA (QUantification tool for Methylation Analysis) program. Outcomes: The main outcome of this study was RIII analysis using bisulfite genomic sequencing. Results: We found sex differences in RIII methylation profiles in cisgender and transgender populations. Cismen showed a higher methylation degree than ciswomen at CpG sites 297, 306, 509, and at the total fragment ( P ≤ .003, P ≤ .026, P ≤ .001, P ≤ .006). Transmen showed a lower methylation level than trans women at sites 306, 372, and at the total fragment ( P ≤ .0001, P ≤ .018, P ≤ .0107). Before the hormone treatment, transmen showed the lowest methylation level with respect to cisgender and transgender populations, whereas transwomen reached an intermediate methylation level between both the cisgender groups. After the hormone treatment, transmen showed a statistically significant methylation increase, whereas transwomen showed a non-significant methylation decrease. After the hormone treatment, the RIII methylation differences between transmen and transwomen disappeared, and both transgender groups reached an intermediate methylation level between both the cisgender groups. Clinical Implications: Clinical implications in the hormonal treatment of trans people. Strengths & Limitations: Increasing the number of regions analyzed in the ESR1 promoter and increasing the number of tissues analyzed would provide a better understanding of the variation in the methylation pattern. Conclusions: Our data showed sex differences in RIII methylation patterns in cisgender and transgender populations before the hormone treatment. Furthermore, before the hormone treatment, transwomen and transmen showed a characteristic methylation profile, different from both the cisgender groups. But the hormonal treatment modified RIII methylation in trans populations, which are now more similar to their gender. Therefore, our results suggest that the methylation of RIII could be involved in gender dysphoria.